Development of Flashcard Worksheet with Academic Competency Test Assessment in Improving Figurative Language Comprehension - Ardhani, Syafira; Purwati, Panca Dewi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Low figurative language comprehension among Grade V elementary school students is caused by the abstract nature of the material, limited engaging learning media, and the absence of standardised assessments to measure figurative language literacy competency. This study aims to develop a flashcard worksheet design assisted by academic competency test assessment, validate its feasibility, and examine its effectiveness in improving students' understanding of figurative language (metaphor, personification, and hyperbole). The study employs the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model with 26 Grade V students of SD Negeri 3 Cepiring, Kendal Regency as subjects. Media were developed using the Canva Application by integrating Demak local wisdom elements, comprising: (1) an A4 main worksheet with 30 validated TKA items; (2) 20 pairs of 5.6 × 8.7 cm flashcards featuring Demak Batik and Grand Mosque motifs; (3) A5 Make a Match instruction cards; and (4) QR Code barcodes linked to digital answer keys. Data were collected through questionnaires, tests, and documentation. Media expert validation yielded 88% (very valid) and material expert validation 95% (very valid), with an average of 91.5% (very valid). Teacher responses reached 100% (very appropriate) and large-scale student responses 95.13% (very appropriate). The effectiveness test showed 69.23% of students achieved learning completeness with an average score of 68.15 and Cronbach's Alpha reliability of 0.907 (very high). Taken together, these findings demonstrate that culturally contextualised, assessment-integrated media can meaningfully raise figurative language literacy in elementary learners who previously lacked both engaging instructional materials and structured competency measures. It is concluded that the flashcard worksheet media assisted by academic competency test assessment, developed based on Demak local wisdom, is valid, practical, and effective in improving Grade V students' figurative language comprehension, and is therefore feasible as an alternative Indonesian language learning medium in elementary schools. Practically, teachers can adopt this media as a ready-to-use instructional tool that simultaneously supports active figurative language learning and prepares students for standardised academic competency assessments, particularly in schools where localised and assessment-aligned resources remain scarce.